Between the crisis and the institutional dismantling: A chapter of recent history, Costa Rica at the dawn of the third millennium - Agüero García, Javier (2019)
This essay constitutes a preliminary interpretation about the crisis and the institutional dismantling of Costa Rica from the year 2000.  For the realization of the analysis, the cases of the Caja Costarricense de Seguro Social, a body dedicated to the provision of health services and health services, are studied. pensions; the educational system, in its primary, secondary and university phases; In addition, Consejo Nacional de Producción, Fábrica Nacional de Licores,  Instituto Nacional de Vivienda y Urbanismo,  Ministerio de Obras Públicas y Transportes, and the Instituto Nacional de Ferrocarriles are addressed; institutions minimized in their scope of action. Under the prism of recent history, sources of information are consulted, such as the reports of the Programa del Informe de la Nación, written and radio press, and telenoticiaries. Finally, the most important challenges faced by these state entities are outlined.